2021
DOI: 10.1093/brain/awab130
|View full text |Cite
|
Sign up to set email alerts
|

Tau mis-splicing correlates with motor impairments and striatal dysfunction in a model of tauopathy

Abstract: Tauopathies are neurodegenerative diseases caused by the abnormal metabolism of the microtubule associated protein Tau, which is highly expressed in neurons and critically involved in microtubule dynamics. In the adult human brain, the alternative splicing of exon 10 in tau pre-mRNA produces equal amounts of protein isoforms with either three (3 R) or four (4 R) microtubule binding domains. Imbalance in the 3 R : 4 R tau ratio is associated with primary tauopathies that develop atypical parkinsonism, such as P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Furthermore, the observed higher levels of pTau were associated with variable levels of total Tau (HT7) across the different brain regions examined. Such hyperphosphorylated-tau/total-Tau ratio changes are not actually novel and have been observed in several Tau-related neurodegenerative conditions 39 , 40 . Generally, hyperphosphorylated-Tau/total-Tau ratio changes are considered to be part of molecular pathomechanisms associated with early neuronal dysfunctions as well as with cognitive and behavioral clinical abnormalities affecting specific neuronal types 25 , 41 43 .…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the observed higher levels of pTau were associated with variable levels of total Tau (HT7) across the different brain regions examined. Such hyperphosphorylated-tau/total-Tau ratio changes are not actually novel and have been observed in several Tau-related neurodegenerative conditions 39 , 40 . Generally, hyperphosphorylated-Tau/total-Tau ratio changes are considered to be part of molecular pathomechanisms associated with early neuronal dysfunctions as well as with cognitive and behavioral clinical abnormalities affecting specific neuronal types 25 , 41 43 .…”
Section: Discussionmentioning
confidence: 80%
“…In previous reports (Espíndola et al, 2018;Damianich et al, 2021) we showed that local modulation of 3R:4R tau isoforms contents into the mPFC or the striatum of htau mice could prevent cognitive or motor coordination deficits, when such modulation was performed at 3 months old, before phenotypic onset. Hence, the most relevant question we aimed to address in this study was if these phenotypes could be rescued, once the deficits were already present.…”
Section: Phenotypic Rescue By Local Tau Isoforms Modulation In Htau Micementioning
confidence: 81%
“…We have previously shown that the SMaRT strategy -spliceosome mediated RNA trans -splicing- ( Rodriguez-Martin et al, 2005 ) is a suitable tool to modulate E10 inclusion in endogenous MAPT transcript, both in mouse and human neurons in culture ( Avale et al, 2013 ; Lacovich et al, 2017 ), and into the adult mouse brain ( Espíndola et al, 2018 ; Damianich et al, 2021 ). To test SMaRT modulation of Tau in vivo , we used the htau mouse model ( Andorfer et al, 2003 ) which expresses a full length wild-type human MAPT transgene in an endogenous Mapt−/− background.…”
Section: Introductionmentioning
confidence: 99%
“…), preventing its aggregation, or enhancing its clearance, to a loss‐of‐function model where normal tau levels and function are restored. The importance of tau in its native configuration is highlighted by the fact that tau knockout models exhibit a neurological phenotype, including dopaminergic dysfunction 21 …”
Section: Figmentioning
confidence: 99%
“…The importance of tau in its native configuration is highlighted by the fact that tau knockout models exhibit a neurological phenotype, including dopaminergic dysfunction. 21 Protein aggregation is a physical problem pertaining to loss of solubility, with sequestration into insoluble cross-β fibers, also known as amyloids. Amyloid aggregation thus represents the end product of the soluble-to-insoluble phase transition of proteins, a functioning-to-nonfunctioning biological change.…”
mentioning
confidence: 99%